2021
DOI: 10.3889/oamjms.2021.5996
|View full text |Cite
|
Sign up to set email alerts
|

Total Penectomy and Perineal Urethrostomy Management of Penile Squamous Cell Carcinoma with Paraffinoma in Single Center Hospital: A Rare Case Report

Abstract: BACKGROUND: Penile cancer is a rare condition, affecting less than 1% of the adult male population [1]. The risk of penile cancer increases significantly with age, poor hygiene, and the presence of the prepuce. The most common type encountered is squamous cell carcinoma (SCC). Clinically penile cancer appears as small lesions with induration and erythema or as large infiltrative ulcerative lesions. As the disease progresses, complaints such as itching, bleeding, discharge, foul odor, and pain occurred. CASE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Owing to its high complication rate and the occurrence of se- rious complications, the once widely used paraffin injection intervention is now considered an abandoned and obsolete procedure. Complications from paraffin injection vary depending on the injection site and can range from a painless lump to ulceration and necrosis, and even cancer and mortality [3,[7][8][9]. The most common complications are soft tissue and skin complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its high complication rate and the occurrence of se- rious complications, the once widely used paraffin injection intervention is now considered an abandoned and obsolete procedure. Complications from paraffin injection vary depending on the injection site and can range from a painless lump to ulceration and necrosis, and even cancer and mortality [3,[7][8][9]. The most common complications are soft tissue and skin complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although paraffin injection was widely used for cosmetic purposes for a long time, it has now become an abandoned procedure due to serious complications. Complications from paraffin injection can range from a painless lump to ulceration and necrosis, and even cancer and mortality [3,[7][8][9]. Generally, most cases do not exhibit any noticeable symptoms initially; however, in some cases, an immediate inflammatory reaction may occur.…”
Section: Introductionmentioning
confidence: 99%
“… 11 In a case of penile squamous cell carcinoma with paraffinoma, Syaeful Agung Wibowo et al described a patient who had previously used silicone injection 35 years prior and developed sclerofibromatosis as a result. 12 The authors suggested that persistent inflammation following silicon injection might increase the risk of penile cancer.…”
Section: Discussionmentioning
confidence: 99%